Research of Authoritarian Structure of Personality as Opposite Tolerant Personality - Kihtyuk, O. V. (Psychological Prospects Journal, 2011)
In the article is reflected the theoretical ground of main parameters the structure of authoritarian personality as opposite to tolerant and empiric research of their display for student young people. The basic sign of this personality is a gravitation to antidemocratic propaganda.
Keywords: authoritarian personality tolerance ethnically tolerant personality